LEFT-SIDED APPENDICITIS IN LATIN AMERICA AND THE CARIBBEAN: A SYSTEMATIC REVIEW OF CASE REPORTS - Fabian A CHAVEZ-ECOS; Mayli M CONDORI-OROSCO; Anahy de la COLINA-SOSA; Sandra S CHAVEZ-MALPARTIDA; Carlos A DAVILA-HERNANDEZ; Alba ZEVALLOS (Arquivos de Gastroenterologia)
ABSTRACT Background: Worldwide, acute appendicitis (AA) is the most frequent cause of acute surgical abdomen. Although typically associated with pain migrating to the right iliac fossa, AA can also manifest with pain in the left lower quadrant, often linked to anatomical anomalies. Latin America and the Caribbean (LAC) have the highest incidence of AA compared to other regions of the world. Objective: To explore the sociodemographic characteristics; clinical characteristics, and postoperative outcomes in patients with left-sided AA in LAC. Methods: We performed a systematic review including PubMed, Scopus, Web of Science, Embase, LILACS, Dialnet, Redalyc, Scielo, and Google Scholar databases. We considered as inclusion criteria case reports of left-sided appendicitis involving specific anatomical anomalies, and studies conducted in LAC. Morevoer, we assessed methodologic quality using Joanna Briggs Institute tool for case reports. Results: A total of 23 patients were included in 23 case reports. Colombia accounted for the majority of left-sided AA cases. The median age was 37 years (8-65). Initial pain location was diffuse abdominal pain (39.1%), pain was refered (n=5; 55.6%) and migrated (n=11; 78.6%) mainly to left iliac fossa. Situs inversus totalis (SIT) was the most prevalent anatomical anomaly (69.6%), while laparotomy emerged as the predominant surgical approach (65.2%). Conclusion: Considering left-sided AA in the diagnosis of adults with diffuse abdominal pain towards the left lower quadrant is crucial. SIT is the primary associated anatomical variation. These emphasize the significance of understanding atypical presentations for effective management in the LAC population.